Efektivitas Kinerja Pegawai Sekretariat DPRK Aceh Singkil Dalam Menjalankan Tugas Dan Fungsi - Derita Tumangger; Irwan Nasution; Agung Suharyanto (Universitas Medan Area, 2023)
The performance of a government agency can be seen from the work of the employee or government apparatus. This study aims to determine the effectiveness of the performance of the Aceh Singkil DPRK Secretariat employees in carrying out their duties and functions. The research method used is qualitative by emphasizing the concept of performance measurement according to Agus Dwiyanto's theory which includes performance factors, namely: Productivity, Service Quality, Responsiveness, Responsibility and Accountability. Data were collected based on data collection techniques with observation, interviews and documentation. The results of this study indicate that the performance of the Aceh Singkil DPRK Secretariat employees viewed from the performance factors of Productivity, Service Quality, Responsiveness and Accountability can be said to be good with optimal work implementation and the Responsibility performance factor cannot be said to be good because there are still some of the employees working not optimal and not disciplined at work.